1994
DOI: 10.1039/c39940001653
|View full text |Cite
|
Sign up to set email alerts
|

trans-1,3-Dithiane-1,3-dioxide, a new chiral acyl anion equivalent for the preparation of masked activated acids: application to the synthesis of α-hydroxy acid derivatives

Abstract: trans-I ,3-Dithiane-l,3-dioxide reacts with high diastereoselectivity with aromatic aldehydes and the 1,3-dithiane-I ,3dioxide moiety can be easily converted to a thiolester without racemisation by carrying out a Pummerer reaction; the thiolester is a group that can be readily transformed into acids, esters, amides, ketones and aldehydes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…[80,81] Based on an initial Pummerer reaction, several enantioenriched derivatives of α-hydroxy acids were readily obtained, as illustrated in Scheme 16. [80,81] Based on an initial Pummerer reaction, several enantioenriched derivatives of α-hydroxy acids were readily obtained, as illustrated in Scheme 16.…”
Section: Ii4 Condensation Onto Carbonyl Derivativesmentioning
confidence: 99%
“…[80,81] Based on an initial Pummerer reaction, several enantioenriched derivatives of α-hydroxy acids were readily obtained, as illustrated in Scheme 16. [80,81] Based on an initial Pummerer reaction, several enantioenriched derivatives of α-hydroxy acids were readily obtained, as illustrated in Scheme 16.…”
Section: Ii4 Condensation Onto Carbonyl Derivativesmentioning
confidence: 99%
“…Chiral sulfoxides derived from 1,3-dithianes and dithiolanes are valuable asymmetric building blocks and chiral auxiliaries for a wide range of organic reactions, 22,23 but the preparation of these compounds in optically pure form is difficult. 24 Bio-oxidations of simple 1,3-dithianes and dithiolanes 5,8,12,16,17 demonstrated that CHMO from Acinetobacter is an important catalyst for this reactions, and our earlier studies, 12 as well as the results presented in this paper, demonstrate that several such compounds, including very useful and highly interesting 2a and 3a, can be prepared using the recombinant organisms overexpressing CHMO.…”
Section: Discussionmentioning
confidence: 99%
“…Taking advantage of the high diastereoselectivity observed with aromatic aldehydes in all these reactions, Aggarwal et al used ( R , R )‐(+)‐1,3‐dithiane 1,3‐dioxide ( 26 ) as starting material in view of preparing enantiopure materials 80,81…”
Section: Anionic Reactivity Of C2‐symmetric Bis(sulfoxides)mentioning
confidence: 99%